Vowels as a morphological tool in Santiago Creole Portuguese (Cape Verde) - (:unkn) unknown (My University, 2001)
In the Republic of Cape Verde (Africa), the official language is standard portuguese, but nonetheless, the whole population of the nine inhabited islands of the Archipelago uses almost exclusively creole portuguese as a common language. Although each island has its own linguistic features and peculiarities, one can easily regroup them into two main dialectal areas. The first area includes the southern islands of Santiago, Maio, Fogo and Brava. These four islands, commonly called Sotavento, concentrate roughly 70 % of the Cape-Verdian people, and their creole portuguese is grammatically and lexically more influenced by west-african languages (principally wolof, mandinga and temne). The other area includes the northern islands, known as Barlavento, and their creole portuguese dialects are much closer to portuguese, in all respects. In the Sotavento area, the creole of Santiago deserves special attention. Effectively, it is both the most widespread dialect in terms of speakers, since its population represents more than 50 % of the Cape-Verdians, and the oldest creole of the archipelago, the island having been settled by the portuguese (quickly followed by black slaves) from the XVth century. Thus, the euro-african language spoken nowadays in Santiago has developed for five centuries, and is presently not understandable, in its rural form, for a speaker of standard portuguese. The native speakers of Santiago creole portuguese usually use the name badiu /bå'diw/ to design themselves or their mother tongue. I chose to anglicize the term under the form badew, which I will use henceforth in this article.
Keywords: African Research